Multilevel and multidimensional features of socioeconomic status and cognitive function in older adulthood: a cross-sectional analysis of the IGNITE studyResearch in context - Jermon A. Drake; Lu Wan; Chaeryon Kang; Peter J. Gianaros; Patricio Solis-Urra; Haiqing Huang; Rebecca Reed; Charles H. Hillman; Eric D. Vidoni; Jeffrey M. Burns; Arthur F. Kramer; Edward McAuley; et al. (The Lancet Regional Health. Americas)
Summary: Background: Lower socioeconomic status (SES) is associated with increased risk of cognitive decline and dementia, yet reliance on singular indicators of SES limits understanding of these relationships. We examined multiple SES characteristics at the individual and area-levels simultaneously in association with diverse cognitive processes in a large, community-dwelling older adult sample. Methods: Data collected at three United States sites (Boston, Pittsburgh, Kansas City) included a comprehensive cognitive assessment comprising measures of episodic memory, executive function, processing speed, working memory, and visuospatial abilities. Multiple SES measures were obtained including area-level (Area Deprivation Index), subjective, and objective SES. We generated a novel objective SES latent factor from measures of income, savings, debt-adjusted savings, and financial stability using full information maximum likelihood to address missing data, and examined cross–sectional associations of SES indicators with each cognitive domain as outcome variables in multivariable regression models. Findings: This study included 648 cognitively unimpaired older adults (69.88 (3.75) years; 71% female). Individual-level objective SES (processing speed, β [95% confidence interval (CI)] = 0.225 [0.152–0.299]; executive function, 0.210 [0.137–0.283]; episodic memory, 0.113 [0.040–0.186]; working memory, 0.200 [0.129–0.271]; visuospatial processing, 0.165 [0.093–0.238]) and subjective SES (processing speed, β [95% CI] = 0.148 [0.077–0.219]; executive function, 0.138 [0.067–0.208]; episodic memory, 0.020 [−0.051 to 0.091]; working memory, 0.128 [0.059–0.197]; visuospatial processing, 0.094 [0.023–0.164]) outperformed area-level SES in detecting cognitive deficits, and demonstrated widespread associations with poorer performance across cognitive domains. On average, individuals categorized into the lowest objective SES quartile performed between 0.22 and 0.58 standard deviations lower than those in the highest quartile across domains (processing speed, pairwise adjusted mean difference [95% CI] = 0.580 [0.304–0.856]; executive function, 0.556 [0.282–0.829]; episodic memory, 0.223 [−0.054 to 0.499]; working memory, 0.516 [0.248–0.784]; visuospatial processing, 0.434 [0.161–0.706]). A novel objective SES composite showed robust associations with cognition above and beyond traditional SES measures. All findings are subject to missing at random assumptions. Interpretation: Standard measures of objective SES may underestimate the broad cognitive burden of socioeconomic inequity. Integrating multiple financial indicators into future studies may improve estimation of the public health impact of socioeconomic conditions in older adulthood. Funding: National Institutes of Health (R01AG053952).